PENERAPAN MODEL PEMBELAJARAN KOOPERATIF TIPE THINK PAIR SHARE (TPS) UNTUK MENINGKATKAN KUALITAS PEMBELAJARAN IPS MATERI MASYARAKAT INDONESIA MASA PRAAKSARA, HINDU-BUDHA, DAN ISLAM PADA SISWA KELAS VII C SMPN 33 BANDAR LAMPUNG - Kartini, Kartini (LPPM STKIP PGRI Bandar Lampung, 2021)
A good teaching and learning process requires students to be more active so that the teaching and learning process must reflect two-way communication, not just providing one-way information from the teacher without developing students' mentality. Less varied learning and does not use the media as a learning aid so that students feel bored and do not participate in social studies learning activities. Based on this problem, researchers used the Think Pair Share learning model to improve the quality of social studies learning materials for Indonesian society during the Praaksara, Hindu-Buddhist and Islamic periods. This type of research is classroom action research. The subjects of this study were 32 students of class VIIC at SMPN 33 Bandar Lampung for the 2018/2019 academic year, consisting of 18 male students and 14 female students. Data collection techniques used test and non-test techniques. This classroom action research was conducted in 2 cycles, each consisting of 2 meetings. Each meeting consists of 4 stages, namely planning, implementing, observing, and reflecting. The results showed that: (1) The application of the Think Pair Share Learning Model in social studies learning can improve teacher skills, this is indicated by the increase in teacher skills in each cycle, the first cycle gets a score of 8 in the good category, increases in the second cycle it gets a score of 11 in the very category. good. (2) the application of the Think Pair Share Learning Model in social studies learning can increase student activity as indicated by the increase in the first cycle, the number of scores of 189 good categories increased in the second cycle, which got a score of 223 in the very good category. (3) The application of the Think Pair Share Learning Model in social studies learning can improve student learning outcomes. In the pre-cycle stage, 25% of student learning completeness or 8 of the 32 students have completed learning. Increased in the first cycle to 59.4% or 19 students from 32 students. In the second cycle it increased again to 81.25% or 26 students from 32 students. (4) The application of the Think Pair Share Learning Model can improve the quality of social studies learning, this is indicated by the improvement of teacher skills, student activities and learning outcomes. The conclusion of this research is that through the Think Pair Share learning model, it can improve social studies learning outcomes of Indonesian Society Material during the Praaksara, Hindu-Buddhist and Islamic periods of class VII SMPN 33 Bandar Lampung 2018/2019. Suggestions for teachers are that teachers need to follow the development of information, especially regarding the use of the latest learning approaches, models, models and strategies, so that teachers can apply them in the classroom and are expected to be able to conduct creative and innovative learning that is able to motivate student activity in learning.